ANALISIS NILAI TAMBAH KACANG SHANGHAI â€œKONENCIâ€ DI PASLATEN KOTA TOMOHON - Chintya Syomi Palohon; Leonardus Ricky Rengkung; Paulus Adrian Pangemanan (Sam Ratulangi University, 2018)
This research aims to determine the magnitude of the added value and benefitsÂ obtained from the home industri of Shanghai Nut Conenci in Paslaten, Tomohon City. ThisÂ research was conducted from March to May 2018, in household businesses in Paslaten Village,Â Tomohon City. The method used in this study, survey method with direct interview techniques toÂ business owners using a list of questions that have been prepared in advance. The resultsÂ showed that the value added of peanuts to Shanghai beans hated from three productionÂ processes a week of Rp 2,094,917, while the added value in each one kilogram of peanuts wasÂ Rp. 41,988, - Benefits of a Shanghai Konenci bean processing business with three the productionprocess amounted to Rp. 69,264. *lrr+eprm*